Studi Kualitatif Tentang Efektivitas Penggunaan LKPD dalam Pembelajaran Agama Islam di MIS Al-Hidayah - Nurmayani Nurmayani; Rendi Prilandi; Dinda Prati Dina Arsah; Fajra Lativa Asri; Sazkyla Nur Efendi; Assha Uli Handayani Hasibuan (Pusat Riset dan Inovasi Nasional, 2025)
This study focuses on how the use of Student Worksheets (LKPD) can support the Islamic Religious Education (PAI) learning process at MIS Al-Hidayah. Using a qualitative approach, researchers explored the experiences of teachers and students through interviews, observations, and documentation. The results indicate that LKPD equipped with visual media can create a more engaging learning environment, motivate students, and facilitate their understanding of the material. Teachers design LKPD with pictures and sequential steps, enabling students to be more active and able to learn independently or in groups. Despite obstacles, such as limited time for development and incomplete school facilities, teacher creativity and collaboration with colleagues proved key to success. These findings confirm that LKPD can be an effective learning tool, not only for improving cognitive understanding but also for instilling Islamic values ​​in students. This study also has implications for the development of PAI learning strategies in madrasah-based elementary schools. Thus, the innovative use of LKPD can become a sustainable learning model to improve the quality of Islamic education in the future.